Comparison Between Numerical Modeling Approaches of Infilled Frames Under In-Plane Load - Bouarroudj, Mohammed Amin; Boudaoud, Zeineddine (Frontiers in Built Environment, 2022)
In the last decades, important attention was given to infill masonry panels due to their worldwide uses. Many experimental and numerical studies were conducted to study their effect on the behavior of RC frames. In general, three modeling strategies are widely applied to model infill masonry, namely, micro-models, meso models, and macro-models. This paper investigates the accuracy of the width models to predict the behavior of masonry infills using meso modeling technique. To this aim, the masonry infills is modeled as an equivalent homogenized diagonal element in order to represent the diagonal action of masonry infills. The width models used to determine the width of the diagonal strut is used in meso modeling. In addition, the study contains comparison between different modeling techniques to predict the global behavior of the infilled frames. Experimental tests conducted on two infilled frames from the literature are considered to calibrate the numerical simulations. The results indicate that the micro-modeling approach gives a good agreement with the experimental tests in terms of lateral force and deformation shapes, the related errors varying between 0.12% and 2.8%. Using single strut models, the differences between numerical and experimental results vary from 1.1% to 20%. On the other hand, the errors obtained from multiple struts models are varying between 9% to 40%.